Work restrictions and Unfitness to work: Prevalence and risk factors a cross-sectional study on 70 000 occupational visits - Luther Dogbla; Cédric Gouvenelle; Anne-Sophie Escobar; Florence Thorin; Jiao Jiao; Marek Zak; Julien S. Baker; Bruno Pereira; Frédéric Dutheil (PLoS ONE, 2026)
Background Few studies have assessed work restrictions and unfitness to work simultaneously, particularly on large populations, and evidence on their main influencing factors remains limited. Objective To assess prevalence and risk factors of work restrictions and unfitness to work. Method We included all visits conducted in occupational health departments of the Cher, over two consecutive years. Visits had to have a conclusion: fitness to work, temporary work restrictions, permanent work restrictions, and unfitness to work. Mixed multinomial models with individual random effects were used. Results Among the 71,848 occupational health visits, 62,436 had a conclusion. Most (90.6%, 95 CI 90.4 to 90.8%) were fit to work, 3.2% (3.1 to 3.3%) had temporary restrictions, 4.9% (4.7 to 5.1%) had permanent restrictions, and 1.3% (1.2 to 1.4%) were unfit to work. The risk of temporary restrictions was multiplied by 1.69 (1.16 to 2.48) in workers over 55 vs < 25 years old; by 1.74 (1.42 to 2.14) in workers with disabilities; by 1.30 (1.07 to 1.58) for workers with 10–20 vs < 5 years of seniority; and by 1.57 (1.22 to 2.01) in companies with 50–199 vs < 10 workers. The risk of permanent restrictions was multiplied by 2.24 (1.68 to 2.97) in workers over 55 yo; by 1.86 (1.57 to 2.21) in workers with disabilities; by 1.47 (1.05 to 2.06) for qualified workers; by 1.24 (1.05 to 1.46) for workers with 10–20 years of seniority; and by 1.30 (1.07 to 1.58) for workers in companies with 50–199 employees. The risk of unfitness to work decreased with increasing seniority in the company, while a significant interaction between sex and sector of activity was observed for temporary restrictions. Conclusion Nearly one worker out of ten were unfit to work or had restrictions. The main risk factors for both unfit to work and restrictions were older age, women, and return-to-work visits; whereas lower seniority and smaller companies were risk factors for unfit to work, and longer seniority and bigger companies were risk factors for restrictions.